Combining approaches for systemic behaviour change in groundwater governance - Sanil, Richu; Falk, Thomas; Meinzen-Dick, Ruth S.; Priyadarshini, Pratiti (Ubiquity Press, Ltd., 2024)
Over-extraction of groundwater is a prominent challenge in India, with profound implication for food security, livelihoods, and economic development. As groundwater is an ‘invisible’ and mobile common pool resource, sustainable governance of groundwater is complex, multifaceted, requiring coordination among various stakeholders at different scales. It remains an open question as to what can be done to strengthen the governance of groundwater, particularly on the scale necessary to address widespread depletion of resources. The growing competition over groundwater resources calls for systemic changes towards sustainable water management. These require understanding the behaviours of actors in the system network, as well as the institutions that shape the direction in which the system moves. In this paper, we offer a behavioural perspective to system transformation and apply it to the example of an Indian NGO working on sustainable natural resource governance. The organisation, Foundation for Ecological Security (FES), has been co-designing and using various institutional tools for groundwater governance with the collaboration of other NGOs and government partners, academic and research organisations towards strengthening governance of water. At the local level, these include groundwater monitoring and crop water budgeting, combined with experiential learning tools such as games for demand management, and supply side interventions to support water harvesting and recharge. These tools are combined with efforts to strengthen multi-actor platforms, building coalitions and capacity of government, civil society and private sector actors to support groundwater governance at scale. By combining local and systemic approaches, the aim is to influence water governance on a larger scale and contribute to the sustainable management of water resources in India. Our reflections illustrate how conceptual thinking can inform multi-methods approaches which consider that sustainably improving groundwater management at large scale requires inter-linked behavioural changes of diverse actors. Our approach constitutes critical reflection and conceptualization, based on situated knowledge which contributes to designing better adapted and more powerful intervention strategies through informed argument.